1978
DOI: 10.1002/cpt1978243343
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of in vivo red cell/plasma Li+ ratios by in vitro methods

Abstract: Two incubation procedures were used for the determination, in vitro, of the steady-state Li+ ratio between red cells and external media. The Li+ ratio in vitro determined prior to Li+ therapy correlates significantly with the subsequent ratio in vivo between red cells and plasma in patients treated with Li+. The Li+ ratio determined in vitro in patients during Li+ therapy was significantly higher than the value determined during the pretreatment, drug-free period that correlated significantly with Li+ ratios i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1979
1979
1985
1985

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…16, 589 (1977 trations were then determined by atomic emission spectrophotometry. This procedure yields a lithium ratio that is highly correlated (r = .85, P < .001) with the lithium ratio in vivo (6). We (E.D., S.E., and R.S.)…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…16, 589 (1977 trations were then determined by atomic emission spectrophotometry. This procedure yields a lithium ratio that is highly correlated (r = .85, P < .001) with the lithium ratio in vivo (6). We (E.D., S.E., and R.S.)…”
mentioning
confidence: 75%
“…Dose-response 'functions were computed fo'r individuals and groups by comparing drug performance to saline performance (mean correct responses after drug divided by mean correct response after saline). 6. Direct infusion of 6-OHDA into neural tissue results in selective 'damage to catecholaminergic neurons or neuron terminals (or both) (16).…”
mentioning
confidence: 99%
“…Similar interindividual differences were observed in this transport which were in correlation with the in vivo steady state RBC/plasma Li ratios Greil et al, 1977). For this reason, an in vitro clinical laboratory test to predict the in vivo Li ratio was proposed by Rybakowski et al (1977) and Pandey et al (1978a).…”
Section: Introductionmentioning
confidence: 60%
“…Measuring this trans port process a high correlation could be observed between the in vitro Nadependent Li flux and the in vivo Li ratio in healthy and manic-depressive persons (Rvbakowski et al, 1977;Greil et al, 1977;Pandey et al, 1978a). It seemed, therefore, of clinical significance to study this transport pathway in different subtypes of affective disorders during prophylactic Li therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Since in vivo RBC/plasma ratios of lithium can be pre dicted by in vitro incubation procedures (16), genetic studies in a large number of subjects can easily be performed. Mendels and Frazer (13) reported that depressed patients who improved with lithium therapy developed higher Li+ ratios than the nonresponders.…”
Section: Genetic Factors In Lithium Transportmentioning
confidence: 99%